IMPLEMENTASI METODE CERTAINTY FACTOR DIGUNAKAN UNTUK IDENTIFIKASI PENYAKIT KULIT ANJING - Prakoso, Raden Karno Bahterang; Maslihah (Melek IT : Information Technology Journal, 2022)
Dogs are one of the favorite animals that are kept by the community, even though there are still many dog ??breeders who still do not know how to treat and maintain a dog's health condition, Knowing the symptoms and types of diseases that are generally accepted by dogs can provide dog care with a fast response to provide treatment when the dog stricken with disease. It is possible that this condition often occurs in dog maintenance beginners due to a lack of understanding about the type of disease and handling when a dog is sick. The certainty factor method is used to build a dog skin disease identification system. Therefore, this study aims to build a certainty factor method used to identify dog skin diseases. And first aid that can be given to pets. From the results of testing the system is successful with a percentage of 100% and by making this expert system application to make it easier to find out diseases in dogs and how to handle them.